Religion and Socioeconomic Wellbeing—Empirical Study of the Impact of Religion on Socioeconomic Rights in the Pluralistic and Democratic Context of Tamil Nadu, India - Anthony, Francis-Vincent 1954-; Sterkens, Carl 1971- (2020)
There is no gainsaying that in a globalized world, economic and technological development greatly determine human wellbeing. In the Indian context, the dialectics between socialist and capitalist economy, while giving way to the latter since 1991, has progressively led to the enlargement of the middle class, yet widened the gap between the rich and the poor. Such a situation points to the importance of socioeconomic rights for guaranteeing human flourishing. The question that we pose is whether religions can play a significant role in favoring these human rights, given their own specific vision of human life and of its socioeconomic facets, such as work, wealth, leisure, health, and education. In other words, can personal and contextual religious attitudes and religious socialization contribute to socioeconomic wellbeing? The empirical research undertaken in the pluralistic and democratic context of Tamil Nadu, India, seeks to verify among 1215 Christian, Muslim, and Hindu students, the impact of religion on their attitude towards socioeconomic rights. The emerging results reveal that some aspects of religious attitudes and socialization have a significant impact on students’ agreement with socioeconomic rights, particularly in the case of Christians and Muslims. We conclude with a discussion on the salient findings and their implications.
Keywords: Christianity; Hinduism; Islam; Democracy; Education; human wellbeing; socioeconomic rights